Web application vulnerabilities detection model - Buja, Alya Geogiana; Abd. Jalil, Kamarularifin; Mohd Ali, Fakariah; Abdul Rahman, Teh Faradilla (2016)
The use of web in daily life is increasing and becoming trend now. As the use of the web is increasing, the use of web application is also increasing. Apparently most of the web application exists up to today have some vulnerability that can be exploited by unauthorized person. Some of well-known web application vulnerabilities are Structured Query Language (SQL) Injection, Cross-Site Scripting (XSS) and Cross-Site Request Forgery (CSRF). By compromising with these web application vulnerabilities, the system cracker can gain information about the user and lead to the reputation of the respective organization. This research aim to solve these issues by developing a detection model for detecting and recognizing the web vulnerabilities based on the defined and identified criteria. In addition, the proposed detection model will be able to generate the report regarding the level of vulnerability of the web application. The research will be carried out by using design string matching algorithm. The algorithm is used in order to match the defined criteria of each web vulnerability with the input information about web application. The evaluation of the proposed method is via detection accuracy of each web vulnerability.